Cultural legitimacy in transnational beauty communication: developing the IMCu framework from K-beauty negotiations in Indonesia’s Urban Heartlands - Afwan, Wahab; Mulyana, Deddy; Dida, Suzanne; Aristi, Nindi (Frontiers in Communication, 2026)
K-Beauty has become highly influential in Southeast Asia’s global aesthetic scene. Yet, little is known about how its gentle messaging is understood in Muslim-majority areas, some of the fastest-growing beauty markets. This research explores how young, digitally engaged consumers in Indonesia’s Urban Heartland, guided by religious values, perceive K-Beauty messaging. Using a mixed-methods approach, including 15 interviews, a focus group of six participants, 16 months of digital ethnography, and observations of e-commerce behaviour, the results show that audience reactions are shaped more by cultural legitimacy than by persuasive messages. This legitimacy arises from two decades of Hallyu’s presence in Indonesia, normalizing Korean aesthetic cues, lowering symbolic barriers, and making K-Beauty’s soft tone emotionally and culturally familiar. The study identifies four mechanisms of cultural negotiation: Cultural Mediation, Ethical Localisation, Emotional Co-Creation, and Selective Hybridisation. These are ways in which Korean signals are aligned with Islamic ethics, social norms, and daily beauty routines. Additionally, four structural factors, Long-Term Cultural Familiarity, Ethical Sensitivity, Emotional Coherence, and Algorithmic Hybridisation, explain a shift from traditional Integrated Marketing Communication (IMC) to a new model called Integrated Marketing Cultural (IMCu), which prioritizes cultural resonance over persuasion. This study provides a theory-based, context-specific framework for understanding communication in Muslim-majority digital spaces. By showing how transnational, soft-aesthetic messages acquire meaning and legitimacy, the IMCu framework enhances transcultural communication studies. It offers practical strategies for global beauty brands aiming for culturally sensitive approaches in emerging Muslim markets.